2021
DOI: 10.9734/afsj/2021/v20i630310
|View full text |Cite
|
Sign up to set email alerts
|

Production, Nutritional Evaluation and Acceptability of Cookies Made from a Blend of Wheat, African Walnut, and Carrot Flours

Abstract: Cookies were developed from composite flour of wheat, African Walnut and Carrot. The wheat flour was substituted at levels of 5%, 10%, 15%, & 20% with African Walnut flour for samples, B, C, D and E, respectively, and with 5% of Carrot flour. The moisture content of the cookies reduced with increase in substitution with walnut flour and carrot flour but there was no significant difference (p>0.05) in the values obtained. The ash content and protein content of the cookies also increased with increased su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 18 publications
(20 reference statements)
6
9
1
Order By: Relevance
“…The result of the physical properties of biscuits showed that supplementation of whole wheat flour with flours from soy okara and tigernut residue gave no significant difference (p > 0.05) in the diameter (38.13–38.17 mm) and height (37.73–37.76 mm) of the samples as they all compared favorably with the control, whereas this effect slightly affected the thickness of the supplemented biscuits from 6.10 mm to 6.17 mm, although some significant differences (p < 0.05) were observed. Similar observations were reported for cookies made with wheat, walnut, and carrot flour [ 26 ].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The result of the physical properties of biscuits showed that supplementation of whole wheat flour with flours from soy okara and tigernut residue gave no significant difference (p > 0.05) in the diameter (38.13–38.17 mm) and height (37.73–37.76 mm) of the samples as they all compared favorably with the control, whereas this effect slightly affected the thickness of the supplemented biscuits from 6.10 mm to 6.17 mm, although some significant differences (p < 0.05) were observed. Similar observations were reported for cookies made with wheat, walnut, and carrot flour [ 26 ].…”
Section: Resultssupporting
confidence: 87%
“…This observation was in line with the report of Porcel et al [ 28 ] who noted a similar decrease in the protein content of wheat biscuits fortified with dry tigernut residue. The values of protein obtained in the present study appear less than the recommended daily requirement for protein (25–30 g/day) for ages 15 and 19 years as recommended by WHO [ 39 ] cited in Kiin-Kabari et al [ 26 ]. This indicates that the frequent eating of this snack may serve to alleviate the problem of protein deficiencies in children, of which are the targets for production of this nutritionally improved product, and for adults who may want to snack on healthy food products.…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…Alebiosu et al [ 62 ], also reported an improvement in the iron content (3.73 mg/100 g–6.50 mg/100 g) of cookies produced from wheat–sorghum–defatted coconut composite flour. Iron is an essential trace element which plays vital roles such as hemoglobin formation and the oxidation of fats, protein, and carbohydrates [ 63 ]. The WHO [ 64 ]’s daily recommended intake of iron for children (6–59 months) is 5.8 mg/100 g. Hence, children can acquire the required iron from consuming samples together with other foods.…”
Section: Resultsmentioning
confidence: 99%